Anterior cruciate ligament injuries in Australian football: should women and girls be playing? You're asking the wrong question. Issue 1 (9th April 2020) - Fox, Aaron; Bonacci, Jason; Hoffmann, Samantha; Nimphius, Sophia; Saunders, Natalie
Abstract : Anterior cruciate ligament (ACL) injuries have been a rising concern in the early years of the women's Australian Football League (AFLW), eliciting headlines of a 'knee crisis' surrounding the league. There has been a focus on female biology as the primary factor driving the high rate of ACL injuries in the AFLW. Emphasising Australian football (AF) as being dangerous predominantly due to female biology may be misrepresenting a root cause of the ACL injury problem, perpetuating gender stereotypes that can restrict physical development and participation of women and girls in the sport. We propose that an approach addressing environmental and sociocultural factors, along with biological determinants, is required to truly challenge the ACL injury problem in the AFLW. Sports science and medicine must therefore strive to understand the whole system of women in AF, and question how to address inequities for the benefit of the athletes.